Linking Satellite-Derived Sea Surface Temperature and Chlorophyll-a to Decapterus Catch Variability in the Banda Sea, Indonesia - Anisa Aulia Sabilah; Yasser Arafat; Muhammad Hery Riyadi Alauddin; Mohammad Roin Najih; Khairul Jamil; Muhammad Maskur; Nurhikmah (Jurnal Studi Perikanan Berkelanjutan, 2026)
Small pelagic fisheries are highly sensitive to oceanographic variability, particularly sea surface temperature (SST) and primary productivity. The Banda Sea, located in eastern Indonesia, represents one of the country’s most productive yet understudied pelagic fishing grounds. This study examines the relationship between satellite-derived SST and chlorophyll-a concentration and the catch variability of Decapterus spp. in the Banda Sea. Monthly fisheries landing data from Banda Fishing Port in 2024 were integrated with Aqua MODIS Level 3–4 SST and chlorophyll-a products using spatial analysis and multiple linear regression. SST ranged from 25.3 to 33.6 °C, while chlorophyll-a concentrations varied between 0.04 and 13.78 mg.m-³, exhibiting strong seasonal patterns. The highest Decapterus catch (740,374 kg) occurred during the first transition season, coinciding with moderate SST and elevated chlorophyll-a levels. Regression analysis revealed strong correlations between catch and SST (r = 0.778) and chlorophyll-a (r = 0.775), indicating a significant influence of oceanographic conditions on fish availability. This study provides one of the first quantitative assessments linking satellite-derived environmental variability to small pelagic fisheries in the Banda Sea. The findings highlight the potential application of satellite-based monitoring to support ecosystem-based and climate-adaptive fisheries management in tropical marine environments.